The Development of Tea Picking Opera in Five Areas of Jiangxi Province - Boonyarutkalin , Thanaphan; Huang, Chunyan (Journal of Roi Kaensarn Academi, 2024)
The purpose of this paper is to explore (1) the performance characteristics and development status of Five Areas Tea Picking Opera in Jiangxi Province. (2) the factors affecting the development of tea-picking opera in Five Areas in Jiangxi Province. (3) to put forward feasible suggestions for the better development of tea-picking operas in Five Areas in Jiangxi Province in the new era. This sample is a random sampling survey of performing artists, successors and amateurs of tea-picking operas in Five Areas in Jiangxi Province, as well as teachers and students majoring in tea-picking operas in colleges and universities. 300 questionnaires were distributed to the subjects, 298 questionnaires were collected, and 15 people were purposefully selected for interviews. The results are as follows: (1) The performing roles of Tea Picking Opera in Five Areas in Jiangxi Province are mainly in Two Dan and One Chou、One Sheng One Dan One Chou (commonly known as Sanjiao Ban), performing with the performance skills of Danxiu tong, Sanzi hua and Aizi bu. The singing mainly adopts Three cavities and One tune( Tea cavity,Lamp cavity, Lu cavity, and Miscellaneous tunes).At present, we are faced with some problems, such as aging personnel, serious brain drain, outdated content, insufficient innovation, shrinking market, reduced audience, insufficient publicity and so on. (2) The course of development, regional culture, inheritors, repertoire and mode of communication all have a positive impact on the change of performance style, development and inheritance of Tea Picking Opera in Five Areas in Jiangxi Province. (3) For the sustainable development of the five Areas Tea Picking Opera in Jiangxi Province in the new era, we need to pay attention to the development process, carry forward the traditional culture, innovate the content and form of the play, build a team of talents, and use the network new media technology to enhance the communication effect.